Mathematical modelling of oleic acid epoxidation via a chemo-enzymatic route-From reaction mechanisms to reactor model - Salmi Tapio; Aguilera Adriana Freites; Lindroos Pontus; Kanerva Liisa (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
The immobilized enzyme lipase acts as an efficient, selective and durable catalyst in the direct transformation of unsaturated carboxylic acids to epoxides, which are used as chemical intermediates and biolubricants. Experimental data obtained from the epoxidation of a model molecule, oleic acid in a laboratory-scale isothermal batch reactor were critically evaluated and mathematically modelled in the most precise way. Several rival surface reaction mechanisms were proposed and rate equations based on these mechanisms were derived. The rate equations were implemented in a multiphase model for the laboratory-scale batch reactor and the kinetic and adsorption parameters included in the rate equations were estimated with non-linear regression analysis. Based on the parameter estimation statistics and chemical knowledge, the most plausible kinetic models for the chemo-enzymatic epoxidation of oleic acid on the immobilized lipase catalyst were selected. The best kinetic models gave a good reproduction of the experimental data. The models can be used to predict the performance of enzymatic epoxidation of unsaturated fatty acids. (c) 2021 The Author(s). Published by Elsevier Ltd. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).